PENGARUH POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS VII DI SMP KRISTEN 2 SALATIGA - Maulita Eka Yuliastuti; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Universitas Negeri Medan, 2019)
This study aims to determine the significance of the effect of parenting patterns in the learning motivation of students grade VII in Christian Middle School 2 Salatiga. This type of research is comparative causal research or it can be called ex post facto research, this research carried out in Christian Middle School 2 Salatiga. Subject of this research subjects were class VII students, amounting to 87 people from class VII A totaling 22 students, class VII B totaling 21 students, class VII C totaling 22 students and class VII D totaling 22 students. The methods for collects the data is by spreading questionnaires about parenting pattern based on Baumrind’s theory amounted to 30 questions, and learning motivation questionnaires based on Uno theory amounted to 25 questions. The data analysis technique used is simple linear regression with the help of the SPSS for Windows version 20. Computer program. Based on the results of the study there is no significant influence on parenting pattern towards the learning motivation of grade VII students in Christian Middle School 2 Salatiga, with parenting pattern only contributing influence of 3.9% with Sig 0.097> 0.050 on learning motivation. While the remaining 96.1% is influenced by other factors not examined in this study.Keyword: Parenting Pattern, Learning Motivation